Heat stress alleviation in lactating buffaloes: Effect on physiological response, metabolic hormone, milk production and composition - DAS, K S; SINGH, J K; SINGH, G; UPADHYAY, R C; MALIK, R; OBEROI, P S (The Indian Journal of Animal Sciences, 2014)
To find out the effect of heat stress alleviation on physiological response, metabolic hormone profiles, milk production and composition in lactating buffaloes during hot-dry (HD) and hot-humid (HH) seasons, 42 lactating Nili-Ravi buffaloes were uniformly divided into 2 groups of 21 each. The treatment (T1) group was supplemented with niacin, yeast, edible oil and provided with curtains, additional ceiling fans and mist fans in the shed. The feeding time, frequency and method for providing concentrate were altered. The control (T0) group buffaloes were kept in separate shed without any nutrient supplementation, modification in microclimate and management. The rectal temperatures, recorded at 10 AM and 3 PM, were significantly lower in treatment group buffaloes than control group under both seasons. Similar trends in pulse rate and respiration rate were recorded among treatment and control group buffaloes in both seasons. Plasma cortisol, T3 and T4 values were almost similar in both control and treatment groups. The average daily milk production was significantly higher in treatment group than control group from starting to the end of the experiment. The average total fat and SNF production in treatment group were significantly higher compared to control group. The overall fat per cent in milk of control group buffaloes was recorded to be 7.71% which was significantly higher than treatment group. It was concluded that nutrient supplementations, microclimate modifications and management alterations together in the form of one package help reducing heat stress.It has beneficial effect on physiological responses, total milk production and composition in lactating buffaloes during hot dry and hot humid summer without affecting cortisol, T3 and T4 profile.